Antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation and preparation method thereof
By designing antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation, the problems of bone resorption and non-degradation of existing bone implant materials are solved, and the safe degradation and bone repair effect of the material in the human body is achieved.
Patent Information
- Application Number
- CN202411645578.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-07
AI Technical Summary
Due to the high elastic modulus of bone implantation, the existing bone implant metal materials have caused stress shielding, causing bone resorption and reduced cortical bone density, and are not degradable. They need to be removed again, increasing the economic and health burden of patients.
An antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation was designed. Through alloy composition design and thermoplastic deformation process, the alloy composition was Zn: 1.8-4.5%, Mn: 0.3-1.8%, Sr: 0.2-1.2%, the balance was Mg, and the Zn/Sr atomic ratio was greater than 2. It existed in the form of Mg14ZnSr phase and Mn elemental substance. The Mn particles were dependent on Mg14ZnSr and grew by extrusion molding.
During the degradation process, this magnesium alloy can significantly accelerate the bone repair process, reduce the risk of bacterial infection, meet the requirements of the strong plasticity, corrosion resistance, biocompatibility and antibacterial properties of the bone implant field, and has no toxic side effects on human tissues, and the degradation rate can be adjusted.
Smart Images

Figure CN119571157A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium alloy biomedical materials, and in particular to an antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation and a preparation method thereof. Background Art
[0002] With the development of economy and the progress of society, musculoskeletal diseases are becoming more and more common. Under the dual effects of population base and aging, the scale of bone implant market in my country has increased year by year. Due to its good mechanical properties and processing properties, the metal materials for bone implants widely used in clinical practice are mainly stainless steel, cobalt-chromium alloy and Ti-6Al-4V alloy, etc., in addition to precious metals such as gold, silver, platinum and titanium-nickel shape memory alloys. These biomedical metal materials have good corrosion resistance and biocompatibility, and can exist for a long time in the human body fluid environment and maintain structural stability. However, the elastic modulus of these medical metal materials is much greater than that of bone tissue, which can easily lead to stress shielding effect of bone tissue around implant materials, causing bone absorption, decreased cortical bone density and other diseases, and the risk of fracture again. Furthermore, the above materials are all non-degradable materials, so when they play a role in the human body, they need to be removed by surgery again (if not removed in time, it may cause inflammatory reaction in patients), which not only increases the economic burden of patients, but also easily causes secondary damage to patients in the process of removing materials.
[0003] Degradable biomaterials are considered to be strong competitors to replace non-degradable biomaterials because of their excellent mechanical properties, their ability to completely degrade after the damaged bone is completely repaired, and their products have no toxic side effects on the body. Currently, the most promising degradable metal materials for clinical application are zinc, iron, magnesium and their alloys. Zinc and its alloys have good corrosion resistance, but their poor mechanical properties, low daily recommended intake (11 mg / d) and high elastic modulus (90 GPa) greatly limit their application in the field of biomaterials; iron and its alloys have good mechanical properties, but their degradation rate in the body is slow, and their corrosion products are less affected by human metabolism, and are likely to cause inflammatory reactions due to accumulation in the human body.
[0004] Magnesium alloys have the following advantages as bone implant materials: (1) elastic modulus of 41-45 GPa close to natural bone; (2) can be completely degraded after implantation; (3) magnesium alloys are antibacterial: the Mg produced by the degradation of magnesium alloys 2+ and OH -It can destroy the normal metabolism of bacteria, thus playing a bactericidal role; (4) Magnesium alloys can promote bone repair: Magnesium alloys can interact with key cells in the bone repair process (such as macrophages, osteoblasts, endothelial cells, etc.), playing a role in promoting bone repair; (5) The daily intake of magnesium is high: its daily intake is as high as 330 mg, which is much higher than the 12.5 and 12 mg of zinc and iron.
[0005] As the most promising biodegradable metal for clinical application, Chinese patent CN112760537A discloses a magnesium alloy comprising 88-93 parts of Mg, 2-6 parts of Zn, 0.2-1 parts of Ca, 0.3-1 parts of Mn, 0.3-1 parts of Sn and 0.7-5 parts of rare earth metals. The invention also discloses a method for preparing the above-mentioned magnesium alloy and its use in the preparation of medical devices. The degradation rate of the magnesium alloy is controllable and it has strong mechanical strength, but the rare earth elements contained therein will cause a series of adverse reactions after degradation. Chinese patent CN114561579A discloses a biodegradable magnesium alloy without rare earth elements, including the following elements by mass percentage: Zn 1.0-5.0%; Mn 0.1-1.0%; Ca 0.1-1.0%; Sr 0.1-1.0%; Sn 0.1-3.0%; Zr 0.1-0.8%; Mg balance, with controllable degradation rate and strong mechanical strength, and no elements harmful to the human body. However, the bone repair function and antibacterial effect of the alloy mainly come from metal magnesium, and the effect is average. Summary of the invention
[0006] Therefore, based on the alloy composition design and the hot plastic deformation process, the present invention proposes an antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation and a preparation method thereof. The specific scheme is as follows:
[0007] An antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation, wherein the specific composition of the alloy is, by mass percentage, 1.8-4.5% Zn, 0.3-1.8% Mn, 0.2-1.2% Sr, and the balance is Mg, wherein the atomic ratio of Zn / Sr is greater than 2, and the ratio of Zn and Sr in the Mg-Zn-Mn-Sr alloy is Mg. 14 ZnSr exists in the form of phase, and Mn exists in the form of Mn single substance.
[0008] The above-mentioned method for preparing the magnesium alloy comprises the following steps:
[0009] Step 1: Prepare the raw materials according to the designed alloy composition, the raw materials are: pure magnesium, pure zinc, Mg-Mn master alloy and Mg-Sr master alloy;
[0010] Step 2: After the raw materials and crucible are polished, they are preheated in an inert gas atmosphere to remove moisture from the surface of the raw materials to ensure safety during the smelting process;
[0011] Step 3: Under a protective atmosphere, put the preheated pure magnesium into a crucible and continue to heat until it is completely melted, then add Mg-Sr master alloy, pure zinc and Mg-Mn master alloy in sequence, stirring after each addition of a raw material;
[0012] Step 4: After all the raw materials are melted, they are filtered using foam ceramics, and the filtered materials are placed in a crucible for graded cooling to obtain an ingot;
[0013] Step 5: After the ingot is taken out of the crucible, it is heat treated in a vacuum furnace and then cooled. The ingot is then preheated and then hot extruded to obtain an extruded material. During the hot extrusion process, the extruded material is quenched online.
[0014] Furthermore, the purity of the raw materials pure magnesium and pure zinc in step 1 is above 99.999%, the Mg-Mn master alloy is Mg-3Mn (i.e., Mn accounts for 3% of the total mass of the alloy), and the Mg-Sr master alloy is Mg-30Sr (i.e., Sr accounts for 30% of the total mass of the alloy), wherein the amount of Zn added is 115-120% of the Zn content in the designed alloy composition, the amount of Mn added is 100-105% of the Mn content in the designed alloy composition, and the amount of Sr added is 100-110% of the Sr content in the designed alloy composition.
[0015] Furthermore, in step 2, the preheating temperature of the raw material and the crucible is 175-255° C., the preheating time is 4-24 hours, and the inert gas is high-purity argon.
[0016] Furthermore, the protective atmosphere in step 3 is a mixed gas of argon and tetrafluoroethane with a volume ratio of 20:1-40:1, the temperature when the Mg-Sr master alloy and pure zinc are added is 680-710°C, the temperature when the Mg-Mn master alloy is added is 720-780°C, the stirring method is up and down and horizontal mechanical stirring, and each stirring time is 2-7min.
[0017] Furthermore, the foam ceramic material in step 4 is magnesium oxide, with a pore size of 10-20 ppi, a diameter of 110-120 mm, and a thickness of 15-22 mm.
[0018] Furthermore, the graded cooling method in step 4 is specifically as follows: first, the crucible containing the material is subjected to a first-stage mist cooling, the mist cooling time is 2-10 minutes, the mist cooling range is from the bottom of the crucible to 1 / 10-1 / 6 of the crucible height from the bottom of the crucible, and the mist cooling method is uniform mist cooling along the circumference of the crucible; then, the crucible is placed in an ice-water mixture for water cooling and mist cooling, the liquid level of the ice-water mixture is the same as the height of the first-stage mist cooling range, the mist cooling height is from the liquid level of the ice-water mixture to 1 / 10-1 / 6 of the crucible height from the liquid level of the ice-water mixture, each mist cooling is 1-2 minutes and then stopped for 1-2 minutes, and this is repeated for 2-5 cycles; finally, the crucible is placed in water with a liquid level of 1 / 2-2 / 3 of the crucible height for cooling.
[0019] Furthermore, in step 5, the heat treatment temperature is 330-380° C., and the heat treatment time is 6-48 hours.
[0020] Furthermore, the preheating temperature of the ingot after heat treatment in step 5 is 280-380°C, the time is 4-16h, the extrusion speed during hot extrusion is 0.2mm / s-1.5mm / s, the extrusion ratio is 8-70:1, and the online quenching method is to perform mist cooling, water cooling and air cooling on the extruded material in sequence at the extrusion outlet.
[0021] The beneficial effects of the present invention are:
[0022] 1. Among the alloy elements involved in the present invention, Zn is one of the essential trace elements for the human body, and it mainly plays the role of improving the compactness of the corrosion product film, strengthening the solid solution, and inhibiting the activity of bacteria; Mn is one of the essential trace elements for the human body, and it is a cofactor of many enzymes in the human body. The addition of Mn can form compounds with impurities such as Fe and Si, which will be filtered out during melt filtration, thereby improving the purity of the alloy ingot, while improving the compactness of the alloy corrosion product layer and regulating energy metabolism; Sr has been used in strontium ranelate for the treatment of osteoporosis, and it mainly plays the role of refining grains and promoting the differentiation of osteoblasts. The components are all essential elements for the human body or elements contained in drugs that have been used clinically to treat orthopedic diseases, and have good safety;
[0023] 2. Different from the existing degradable magnesium alloys containing both Zn and Sr elements, the Zn and Sr phases in the present invention are Mg 14 The ZnSr phase exists, and Mn does not form a phase with Mg, Zn, and Sr elements. 14 The micro-galvanic couple of the ZnSr phase (where Mn acts as the cathode in the micro-galvanic couple and Mg 14 ZnSr phase as anode), and the Mn particles and Mg 14 The dependent growth of ZnSr phase is beneficial to the degradation of Zn 2+ and Sr2+ Can be released simultaneously, significantly accelerating the process of bone repair while reducing the risk of bacterial infection;
[0024] 3. The magnesium alloy material for bone implantation meets the requirements of the bone implantation field for material strength-plasticity matching, corrosion resistance, biocompatibility and antibacterial properties. It has no toxic side effects on human tissues, has a controllable degradation rate and has a significant inhibitory effect on bacterial activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0026] Figure 1 The results of scanning electron microscopy of the as-cast alloy in the examples;
[0027] Figure 2 The results of X-ray diffraction of the cast alloy in the embodiment;
[0028] Figure 3 The results of scanning electron microscopy of the extruded alloy in the embodiment;
[0029] Figure 4 is the stress-strain curve of the extruded alloy in the embodiment;
[0030] Figure 5 The microscopic morphology of the tensile fracture of the extruded alloy in the embodiment;
[0031] Figure 6 is the antibacterial rate of the extruded alloy in the embodiment;
[0032] Figure 7 : is the electrochemical polarization curve of the extruded alloy in the example. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Embodiment 1:
[0035] Step 1: According to the designed alloy composition: the mass ratio is Zn:Mn:Sr=3:0.4:0.5, the balance is Mg (recorded as Mg-3Zn-0.4Mn-0.5Sr), the raw materials are batched, wherein the yield of pure zinc is 95%, the yield of Mg-3Mn is 100%, and the yield of Sr in Mg-30Sr is 80%. Excessive batching is performed according to the yield, and the raw materials are: 8378g of pure magnesium (5N), 322g of pure zinc (5N), 212g of Mg-30Sr master alloy (where Sr accounts for 30% of the total mass of the alloy), and 1361g of Mg-3Mn master alloy (where Mn accounts for 3% of the total mass of the alloy);
[0036] Step 2: After grinding the raw material and the crucible, remove the surface oxide scale, and preheat them in an inert gas argon atmosphere. The raw material and the crucible are preheated in an argon atmosphere at a preheating temperature of 195°C for 15 hours to remove water vapor on the surface of the raw material;
[0037] Step 3: Under the protective atmosphere of a mixed gas (tetrafluoroethane:argon) with a volume ratio of 1:15, put the preheated pure magnesium into the crucible and continue to heat it. The temperature is set to 620°C. After keeping warm for 10 minutes, continue to raise the temperature to 710°C until it is completely melted and the temperature reaches 710°C. Then, add Mg-30Sr intermediate alloys to the completely molten magnesium in sequence. After adding, stir and scrape the slag for 4.5 minutes. After the Mg-30Sr intermediate alloy is completely melted, add high-purity zinc (5N). After adding, stir and scrape the slag for 4 minutes. After the pure zinc is melted, continue to raise the temperature and set the temperature to 763°C. After reaching the set temperature and the pure zinc is completely melted, start adding Mg-3Mn intermediate alloy. After adding, stir and scrape the slag for 3 minutes.
[0038] Step 4: After all the intermediate alloys are melted, the foam ceramic (pore size of 20ppi, diameter of 115mm, thickness of 20mm) is first placed in a crucible 28mm above the melt surface and allowed to stand for 3min for preheating to prevent rapid heating from damaging the foam ceramic, and then the foam ceramic is pressed down for melt filtration; after filtration, the bottom of the crucible is first mist-cooled to 1 / 9 of the height of the crucible from the bottom of the crucible, and the mist-cooling time is 7min, and then the crucible is transferred to an ice-water mixture with a liquid level of 1 / 9 of the height of the crucible, and the liquid surface of the ice-water mixture is mist-cooled to 1 / 9 of the height of the crucible above the liquid surface, and the mist-cooling is stopped for 1min every time the mist is cooled for 1min, and this is repeated for 5 cycles, and finally the crucible is placed in water with a liquid level of 1 / 2 of the height of the crucible for cooling;
[0039] Step 5: After taking the ingot out of the crucible, heat treat the ingot. The vacuum furnace temperature is set to 370°C and the heat treatment time is set to 36 hours. After the heat treatment, take out the ingot and water cool it. Before hot extrusion, the ingot is preheated in a vacuum furnace. The preheating temperature is 330°C, the preheating time is 6 hours, the extrusion speed is 0.8 mm / s, the extrusion ratio is 40:1, and graded online cooling is performed near the extrusion outlet: mist cooling, water cooling, and air cooling.
[0040] Embodiment 2:
[0041] Step 1: According to the designed alloy composition: the mass ratio is Zn:Mn:Sr=3:0.7:0.5, and the balance is Mg (recorded as Mg-3Zn-0.7Mn-0.5Sr), the raw materials are batched, wherein the yield of pure zinc is 95%, the yield of Mg-3Mn is 100%, and the yield of Sr in Mg-30Sr is 80%. Excessive batching is performed according to the yield, and the raw materials are: 7360g pure magnesium (5N), 322g pure zinc (5N), 212g Mg-30Sr master alloy, and 2319g Mg-3Mn master alloy;
[0042] Step 2: After grinding the raw material and the crucible, remove the surface oxide scale, and preheat them in an inert gas argon atmosphere. The raw material and the crucible are preheated in an argon atmosphere at a preheating temperature of 205°C for 18 hours to remove water vapor on the surface of the raw material;
[0043] Step 3: Under the protective atmosphere of a mixed gas (tetrafluoroethane:argon) with a volume ratio of 1:20, put the preheated pure magnesium into the crucible and continue to heat it. The temperature is set to 610°C. After keeping warm for 5 minutes, continue to raise the temperature to 700°C until it is completely melted and the temperature reaches 700°C. Then, add Mg-30Sr intermediate alloys to the completely molten magnesium in sequence. After adding, stir and scrape the slag for 3 minutes. After the Mg-30Sr intermediate alloy is completely melted, add high-purity zinc (5N). After adding, stir and scrape the slag for 3 minutes. After the pure zinc is melted, continue to raise the temperature and set the temperature to 750°C. After reaching the set temperature and the pure zinc is completely melted, start adding Mg-3Mn intermediate alloy. After adding, stir and scrape the slag for 3 minutes.
[0044] Step 4: After all the master alloys are melted, first place the foam ceramic (pore size of 15ppi, diameter of 115mm, thickness of 20mm) in the crucible 30mm above the melt surface and let it stand for 4min, then press the foam ceramic down to filter the melt; after filtering, first mist-cool the bottom of the crucible to 1 / 10 of the crucible height from the bottom of the crucible, the mist-cooling time is 5min, then transfer the crucible to an ice-water mixture with a liquid level of 1 / 10 of the crucible height, and mist-cool the liquid surface of the ice-water mixture to 1 / 10 of the crucible height above the liquid surface, mist-cool for 2min and stop for 1min, repeat this for 4 cycles, and finally place the crucible in water with a liquid level of 2 / 3 of the crucible height to cool;
[0045] Step 5: After taking the ingot out of the crucible, heat treat the ingot. The vacuum furnace temperature is set to 370°C and the heat treatment time is set to 24h. After the heat treatment, take out the ingot and water cool it. Before hot extrusion, the ingot is preheated in a vacuum furnace. The preheating temperature is 330°C, the preheating time is 8h, the extrusion speed is 0.5mm / s, the extrusion ratio is 70:1, and graded online cooling is performed near the extrusion outlet: mist cooling, water cooling, and air cooling.
[0046] The alloys in Example 1-2 were subjected to structural observation and performance testing, and the results are as follows:
[0047] Figure 1 :(a) Cast Mg-3Zn-0.4Mn-0.5Sr; (b) Cast Mg-3Zn-0.7Mn-0.5Sr. With the increase of Mn content, the second phase of the alloy Mg 14 The number of ZnSr phases increases, and the continuously distributed second phase can hinder the extension of corrosion.
[0048] Figure 2 :There are α-Mg and Mg in the alloy 14 ZnSr phase, and the increase of Mn content leads to Mg 14 The diffraction peak intensity of the ZnSr phase increases, which is consistent with Figure 1 The results are consistent.
[0049] Figure 3 :(a) Extruded Mg-3Zn-0.4Mn-0.5Sr; (b) Extruded Mg-3Zn-0.7Mn-0.5Sr. After extrusion, the Mn particles and Mg 14 ZnSr grows dependently, which is Zn 2+ and Sr 2+ Provides conditions for release through galvanic corrosion.
[0050] Figure 4: (a) Extruded Mg-3Zn-0.4Mn-0.5Sr; (b) Extruded Mg-3Zn-0.7Mn-0.5Sr. After extrusion, the yield strength of both alloys is greater than 250MPa, the tensile strength is greater than 260MPa, and the elongation is greater than 15%.
[0051] Figure 5 : (a) Extruded Mg-3Zn-0.4Mn-0.5Sr; (b) Extruded Mg-3Zn-0.7Mn-0.5Sr. There are a large number of dimples in the tensile ports of both alloys, indicating that the material has good plasticity and elongation, which is conducive to its use as a bone implant material.
[0052] Figure 6 is the antibacterial rate of the extruded alloy, and the antibacterial rate of the alloy is above 90%, which indicates that the alloy has a strong inhibitory effect on bacterial activity.
[0053] Figure 7 The electrochemical polarization curves of the extruded alloys show that both alloys have a small corrosion current density and have good application prospects.
[0054] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. An antibacterial Mg-Zn-Mn-Sr magnesium alloy for bone implantation, characterized in that: The specific composition of the alloy is as follows: Zn: 1.8-4.5%, Mn: 0.3-1.8%, Sr: 0.2-1.2%, and the balance is Mg. In the Mg-Zn-Mn-Sr alloy, Zn and Sr are in the ratio of Mg. 14 ZnSr exists in the form of phase, and Mn exists in the form of Mn single substance.
2. A method for preparing a magnesium alloy as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Prepare the raw materials according to the designed alloy composition, the raw materials are: pure magnesium, pure zinc, Mg-Mn master alloy and Mg-Sr master alloy; Step 2: After polishing the raw material and the crucible, preheat them in an inert gas atmosphere to remove moisture on the surface of the raw material; Step 3: Under a protective atmosphere, put the preheated pure magnesium into a crucible and continue to heat until it is completely melted, then add Mg-Sr master alloy, pure zinc and Mg-Mn master alloy in sequence, stirring after each addition of a raw material; Step 4: After all the raw materials are melted, they are filtered using foam ceramics, and the filtered materials are placed in a crucible for graded cooling to obtain an ingot; Step 5: After the ingot is taken out of the crucible, it is heat treated in a vacuum furnace and then cooled. The ingot is then preheated and then hot extruded to obtain an extruded material. During the hot extrusion process, the extruded material is quenched online.
3. The method for preparing a magnesium alloy according to claim 2, characterized in that: The purity of the raw materials pure magnesium and pure zinc in step 1 is above 99.999%, the Mg-Mn master alloy is Mg-3Mn, and the Mg-Sr master alloy is Mg-30Sr, wherein the amount of Zn added is 100-112% of the Zn content in the designed alloy composition, the amount of Mn added is 100-106% of the Mn content in the designed alloy composition, and the amount of Sr added is 117-127% of the Sr content in the designed alloy composition.
4. The method for preparing a magnesium alloy according to claim 2, characterized in that: In step 2, the preheating temperature of the raw materials and the crucible is 175-255° C., the preheating time is 4-24 hours, and the inert gas is high-purity argon.
5. The method for preparing a magnesium alloy according to claim 2, characterized in that: The protective atmosphere in step 3 is a mixed gas of argon and tetrafluoroethane in a volume ratio of 20:1-40:
1. The temperature when pure magnesium is added is 600-630°C, the temperature when Mg-Sr master alloy and pure zinc are added is 680-710°C, and the temperature when Mg-Mn master alloy is added is 720-780°C. The stirring method is upper and lower and horizontal mechanical stirring, and each stirring time is 2-7min.
6. The method for preparing a magnesium alloy according to claim 2, characterized in that: The foam ceramic material in step 4 is magnesium oxide, and its pore size is 10-20ppi.
7. The method for preparing a magnesium alloy according to claim 2, characterized in that: The graded cooling method in step 4 is specifically as follows: first, the crucible containing the material is subjected to a first-stage mist cooling, the mist cooling time is 2-10 minutes, the mist cooling range is from the bottom of the crucible to 1 / 10-1 / 6 of the crucible height from the bottom of the crucible, and the mist cooling method is uniform mist cooling along the circumference of the crucible; then, the crucible is placed in an ice-water mixture for water cooling and mist cooling, the liquid level of the ice-water mixture is the same as the height of the first-stage mist cooling range, the mist cooling height is from the liquid level of the ice-water mixture to 1 / 10-1 / 6 of the crucible height from the liquid level of the ice-water mixture, each mist cooling is 1-2 minutes and then stopped for 1-2 minutes, and this is repeated for 2-5 cycles; finally, the crucible is placed in water with a liquid level of 1 / 2-2 / 3 of the crucible height for cooling.
8. The method for preparing a magnesium alloy according to claim 2, characterized in that: The heat treatment temperature in step 5 is 330-380° C., and the heat treatment time is 6-48 hours.
9. The method for preparing a magnesium alloy according to claim 2, characterized in that: The preheating temperature of the ingot after heat treatment in step 5 is 280-380°C, the time is 4-16h, the extrusion speed during hot extrusion is 0.2mm / s-1.5mm / s, the extrusion ratio is 8-70:1, and the online quenching method is to perform mist cooling, water cooling and air cooling on the extruded material in sequence at the extrusion outlet.
Citation Information
Patent Citations
Magnesium alloy and preparation method and use thereof
CN112760537A
Biodegradable magnesium alloy free of rare earth elements as well as preparation method and application of biodegradable magnesium alloy
CN114561579A